The house with a clock in its walls [videorecording (DVD)] - Black, Jack, 1969-; Blanchett, Cate, 1969-; Vaccaro, Owen, 2005-; MacLachlan, Kyle, 1959-; Bellairs, John (Universal Pictures Home Entertainment, 2018)
This magical adventure tells the spine-tingling tale of 10-year-old Lewis, who goes to live with his uncle in a creaky old house with a mysterious tick-tocking heart. But his new town's sleepy façade jolts to life with a secret world of warlocks and witches. Based on the beloved children's classic book.